Age-period-cohort analysis of self-harm incidence rates by gender in Iran among individuals aged 10–39 years, 1990–2019 - Yousef Ramazani; Alireza Abdi; Shahab Rezaeian; Farid Najafi; Zhyla Aliyavari; Mehdi Moradinazar (Scientific Reports)
Abstract This study investigates trends and patterns in self-harm incidence rates among individuals aged 10–39 years in Iran from 1990 to 2019. Using Age-Period-Cohort (APC) analysis, it aims to identify significant age, period, and cohort effects, and to highlight gender-specific trends for effective prevention strategies. Utilizing data from the Global Burden of Disease (GBD) study, we performed an APC analysis to assess trends in self-harm incidence rates by gender. Data was stratified into six age groups and six five-year periods, and analyzed using the APC Web Tool from the National Cancer Institute. The average incidence rates of self-harm attempts and deaths among individuals aged 10–39 years were 93.87 and 7.55 per 100,000 individuals, respectively. Females had 1.75 times higher attempt rates than males, while males had 1.62 times higher death rates. The APC analysis revealed that males experienced stable self-harm rates over time, while females showed a significant decline. Peak incidence for both genders occurred at age 22.5 years. Self-harm incidence rates show younger females are more vulnerable to self-harm, but there has been a general decline in incidences over time, particularly for more recent cohorts but the stability of rates across ages and the lower rates in more recent cohorts highlighted in male.